Accurate positioning of extracorporeal membrane oxygenation cannulas using real-time trans-thoracic echocardiography. (September 2020) - Galante, Ori; Almog, Yaniv; Rainey, Eli; Fuchs, Lior
In this retrospective observational case series, we aimed to evaluate the use of real-time trans-thoracic echocardiography in accurate positioning of extracorporeal membrane oxygenation cannulas. Patients admitted to the intensive care unit with severe adult respiratory distress syndrome in need for extracorporeal membrane oxygenation were screened. Twenty-one extracorporeal membrane oxygenation cannulas were inserted in 10 patients, and 95% of the cannulas were located exactly at the vena cava–right atria junction as planned. Real-time point-of-care trans-thoracic echocardiography for the exact positioning of extracorporeal membrane oxygenation cannula is feasible, simple, time saving, and accurate.